2014
DOI: 10.1214/13-aap949
|View full text |Cite
|
Sign up to set email alerts
|

On the existence of accessible paths in various models of fitness landscapes

Abstract: We present rigorous mathematical analyses of a number of wellknown mathematical models for genetic mutations. In these models, the genome is represented by a vertex of the n-dimensional binary hypercube, for some n, a mutation involves the flipping of a single bit, and each vertex is assigned a real number, called its fitness, according to some rules. Our main concern is with the issue of existence of (selectively) accessible paths; that is, monotonic paths in the hypercube along which fitness is always increa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
93
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(101 citation statements)
references
References 13 publications
6
93
0
1
Order By: Relevance
“…For this reason we here use a slight generalization of the Kimura formula, which reads 7Tf(s) = 1 -e ks. (35) For k -» oo we thus recover the case of the RAW studied in the previous sections, whereas for 7->0we obtain the Haldane-type fixation dynamics that is usually considered in the SSWM literature [4][5][6][7][19][20][21], As before, we consider the limit of infinite L. In this case, we expect that effectively all possible values of the random fit ness components should appear with their appropriate weights. Since the fixation probability of a beneficial mutation with random component y in the uphill direction is t c f{y -x + c), where x is the random component of the current genotype, we find the recursion relation for Q/(y) as [19,20,22] Qi+\(y)…”
Section: Finite Fixation Probabilitymentioning
confidence: 55%
See 2 more Smart Citations
“…For this reason we here use a slight generalization of the Kimura formula, which reads 7Tf(s) = 1 -e ks. (35) For k -» oo we thus recover the case of the RAW studied in the previous sections, whereas for 7->0we obtain the Haldane-type fixation dynamics that is usually considered in the SSWM literature [4][5][6][7][19][20][21], As before, we consider the limit of infinite L. In this case, we expect that effectively all possible values of the random fit ness components should appear with their appropriate weights. Since the fixation probability of a beneficial mutation with random component y in the uphill direction is t c f{y -x + c), where x is the random component of the current genotype, we find the recursion relation for Q/(y) as [19,20,22] Qi+\(y)…”
Section: Finite Fixation Probabilitymentioning
confidence: 55%
“…The m utational pathways follow ed by the RAW are monotonically increasing in fitness, and a num ber o f papers have explored the conditions for the existence o f such selectively accessible paths [ 12,34,35]. In particular, in [35] it was proven that accessible paths to the reference sequence Cr exist in the RM F with a probability approaching unity for L -> oo and any c > 0.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The probability for the existence of fitness-monotonic pathways in the RMF model has been investigated previously for the case when the paths end at the global fitness maximum , and it has been shown that such paths exist with unit probability for large L and any c . 0 (Hegarty and Martinsson 2014). It is not clear whether this result applies in the present setting, however, because the probability that the global maximum coincides with the reference sequence vanishes for large L (see Equation A29).…”
Section: Crossing Probabilitymentioning
confidence: 80%
“…Using an approach similar to that of the present work, an explicit expression for the expected number of accessible pathways in the RMF model with Gumbeldistributed randomness can be derived (Franke et al 2010. Subsequently Hegarty and Martinsson (2014) presented a rigorous proof that accessible pathways exist with unit probability for large L in the RMF model for any c . 0, independent of the distribution of the random fitness component.…”
Section: Landscape Topographymentioning
confidence: 89%